Working relationship problems for the state in Colombia arising from the conduct of notice 001 of 2005 by the national commission on civil service (2013)
Brief analysis of the problem of state employment relationship in Colombia resulting from the completion of the Convocatoria 001 of 2005 by the Comisión Nacional del Servicio Civil and from a practical perspective, recommend procedural improvements to support, accelerate and certify the selection process in our country.